Meacham Park: how do Blacks experience policing in the suburbs? - Boyles, Andrea S. (Kansas State University, 2012)
Historically, relationships between police and residents in minority communities have often been contentious. However most of the literature on race, place, and policing has focused on the policing of Blacks and their interactions with the police in urban settings. Building on this work, this study aims to capture similar processes of racialized policing as they occur in the suburbs. This project expands our understanding by exploring policing as it is carried out in a marginalized Black enclave located in a predominately white middle class suburb. Specifically, I focus on Meacham Park, which is a segregated enclave annexed to the nearby white community of Kirkwood, Missouri. Drawing on interviews with thirty African-American residents of Meacham Park, I explore how residents experience policing and their attitudes toward the police. The interviews reveal a contentious history of relations between residents and the police, and I discuss respondents’ accounts of specific experiences with police surveillance, harassment, and (in some cases) misconduct. However, though many respondents reported extremely negative attitudes toward the police, the great majority also reported at least some positive interactions and experiences. This study extends research on the policing of minority communities into a segregated suburban context and offers implications for improving relations between the police and minority communities.
Keywords: Race; Place; Policing; Qualitative; Sociology (0626)